Broadband Wireless Communications : Transmission, Access and Services - Luise, Marco (Springer London, 1998)
Broadband Wireless Access is a highly challenging and fast changing area of multimedia radio communications. These papers on the subject are the proceedings of the 9th Tyrrhenian Workshop, held in Lerici, Italy, September 1997. They provide a prospect on the state of the art and future development, with a sufficiently wide focus to cover technological, architectural and regulatory issues. Emphasis is given to those advances of digital signal processing techniques, microwave mono lithic integrated circuits and smart antennae that will allow the design of low cost user terminals with advanced capabilities. Specific attention is also devoted to the protocols these new terminals will use to access the radio medium, and to the kind of services that will eventually be provided to the end-user in the future. With contributions from worldwide experts, the material presented here is a timely and high-level overview of the field, and as well as being informative is a useful tool for promoting further investigation into the area of multimedia radio communications.